Feasibility Study for Biogas Generation from Household Digesters in Bangladesh: Evidence from a Household Level Survey - Salam, Samira; Parvin, Rehana; Salam, Md. Abdus; Azad, S. M. Nasim (International Journal of Energy Economics and Policy, 2020)
Biogas could be an important alternative source of energy in order to meet its increasing demand in Bangladesh. To explore the feasibility of biogas generation in Bangladesh, a household level sample survey on the biogas digester adaptors and biogas digester non-adaptors were conducted. The study revealed that costs for cooking by using solid fuels are significantly higher compared to costs for cooking by using biogas. Biogas generation has become very urgent in Bangladesh because of absence of natural gas supply in rural households, collection of fuelwoods has become difficult because of increasing tremendous pressure on forest lands, and the cost of alternative cooking fuels like LP gas is unaffordable for rural people. As the substrates for biogas generation are readily available and people are highly interested to adapt biogas digester, a welcoming environment for biogas generation is prevailed in Bangladesh. Moreover, biogas digesters are easy to operate and easy to maintain and even women can operate and maintain biogas digesters. Biogas production is profitable, and almost all the biogas adopters are satisfied with the performance of biogas digestors. Logistic regression analysis identified some important factors that are significantly influenced for the adoption of biogas digestors and these are (i) education of household head, (ii) household income, (iii) costs for cooking fuels, (iv) number cattle available in the households, and (v) number of poultry available in the households. Results presented in this study indicate that Bangladesh is urgently needed to generate biogas and feasible environment for biogas generation prevails in Bangladesh. The only needs are the motivation, initiatives and necessary support from the top levels to install biogas digesters. Keywords: Biogas, Solid fuels, Anaerobic Digestion, Methane, Renewable energy, Environment. JEL Classifications: Q4, P28 DOI: https://doi.org/10.32479/ijeep.9206